Safety Vehicle Explanation to Youth in State 1 High School of Tabanan - Rahmat Ahmad; Riz Rifai Oktavianus Sasue; Adrian Pradana; Asep Eka Nugraha; Yusime Fitasari; Akbar Zulkarnain (Jurnal Pengabdian Kepada Masyarakat Semangat Nyata Untuk Mengabdi (JKPM Senyum), 2022)
Accidents can happen anytime and anywhere without us knowing. Ignorance and ignorance of drivers regarding safety aspects when driving is something that must be addressed. Data obtained from the Korlantas Polri in 2021 the number of accidents from 2016 to 2020 involving motorbikes was 74.54% where the age of the victims included students, students and young workers as many as 56,187 people or 43.06%. Driving safety is very important for us to know and implement as soon as possible to reduce the number of accidents. Educating the public on the importance of safe driving is very necessary in order to provide education to the community, especially those who are still teenagers. Community Service Activities (PkM) were carried out at SMAN 1 Tabanan with the method of counseling participants. The participants of this PkM activity are students from the school. Participants will be given material related to technical aspects and vehicles that are safe on the highway in the hope of increasing participants' knowledge regarding technical aspects and aspects of driving safety.